Concreto com agregado reciclado reforçado com fibras de aço: revisão da literatura e avaliação de modelos analíticos - Gazoni, Murilo Henn (2022)
The development of new concrete technologies has accelerated in recent years, combining performance and demand for sustainability. Therefore, the development of a steel fiber reinforced concrete and produced with replacement of the natural coarse aggregate by recycled aggregate is perfectly suited to this context. Due to the more porous nature and crushing process that originates the recycled aggregate, the use of steel fibers in the mixture mitigates the negative effects due to the presence of recycled aggregate in concrete, creating the steel fiber reinforced recycled concrete. Considering that discussions about this type of concrete are a relatively new field, the fundamental objective of this study was to describe the current knowledge on the subject, providing an overview of its mechanical behavior, contemplating the effects of recycled aggregate and fibers on workability and concrete strength. A systematic review on recycled concrete reinforced with steel fibers was carried out; studies about the use of recycled aggregate, steel fibers and evaluated the resistant behavior of concrete were selected. Once the references that fit the scope of this study were selected, the main findings on the influence of recycled aggregate combined with steel fiber on the compressive and tensile strength of concrete, modulus of elasticity and workability of recycled concrete reinforced with steel fibers were presented and discussed. The presence of recycled aggregate causes a reduction in the compressive strength and elasticity modulus of concrete; for substitutions above 50% the effects are more pronounced. Also, the incorporation of steel fibers promotes a reduction in the workability of the mixture, a significant increase in the tensile strength and, indirectly, an increase in the compressive strength of the concrete. Mineral additions and self-compacting concretes were also beneficial for increasing compressive strength and improving concrete workability, respectively. The systematic review also revealed that analytical models for predicting the mechanical properties of this concrete are based on the strength of the reference concrete, volume of recycled aggregate and volume of steel fibers incorporated into the mixture. The models found allowed estimating the compressive and tensile strength as well as the elastic modulus of steel fiber reinforced recycled concrete. The predicted values were compared to values available in the literature. The predicted compressive strength was in agreement correlation with the experimental values, while the tensile strength was overestimated by analytical model.